2017
DOI: 10.1007/s10068-017-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ripening conditions on the physicochemical and antioxidant properties of tomato (Lycopersicon esculentum Mill.)

Abstract: This study was conducted to assess the physicochemical changes and overall nutritional implications of greenhouse-grown "TY Megaton" and "Yureka" tomato cultivars under on-vine and postharvest ripening conditions. In the first group, tomatoes were harvested from a vine at the breaker, pink, and red ripening stages and sampled immediately. The second group was harvested at the breaker stage and allowed to ripen under room conditions to the pink and red stages based on color values, similar to the vine-ripened s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…In this study, the weight loss values of all the three maturity stages of both cultivars were found lower than those suggested by Nunes ( 2008) and Getinet et al (2008) at the end of storage period; it could be due to the storage at the recommended temperature (12°C) with proper management of RH at 85 ± 5%. Considering the significant difference between cultivars on weight loss in the present study and as reported by Tilahun, Park, et al (2017a) for the same cultivars, it could be explained that tomato cultivars markedly vary in response to weight loss at different maturity stages.…”
Section: Weight Loss and Firmnesssupporting
confidence: 75%
See 3 more Smart Citations
“…In this study, the weight loss values of all the three maturity stages of both cultivars were found lower than those suggested by Nunes ( 2008) and Getinet et al (2008) at the end of storage period; it could be due to the storage at the recommended temperature (12°C) with proper management of RH at 85 ± 5%. Considering the significant difference between cultivars on weight loss in the present study and as reported by Tilahun, Park, et al (2017a) for the same cultivars, it could be explained that tomato cultivars markedly vary in response to weight loss at different maturity stages.…”
Section: Weight Loss and Firmnesssupporting
confidence: 75%
“…The trend observed for Hunter a* in the present study was similar to the trend observed for lycopene content. Arias, Lee, Logendra, and Janes (2000) and Tilahun, Park, et al (2017a) also reported a direct correlation of lycopene Los resultados se presentan como medias ± desviación estándar (n꞊5). Los valores con distintas letras al interior de la misma columna son significativamente diferentes (p < 0.05).…”
Section: Color Changesmentioning
confidence: 81%
See 2 more Smart Citations
“…According to Giovanelli et al (1999), ripening conditions affected both the antioxidant accumulation kinetics and final content; tomato fruits picked at the full ripe stage, had lower level of antioxidants (lycopene, β-carotene and ascorbic acid) than those picked at mature green stage and ripened off vine. However, Tilahun et al (2017b) reported that breaker-stage tomatoes can be postharvest-ripened under room conditions without affecting their marketability and nutritional components.…”
Section: Ripening Conditionsmentioning
confidence: 99%